Validation of the "Muslims' Perceptions And Attitudes To Mental Health Scale (M-PAMH)" into Malay: a preliminary study - Zulkifli, Najhan Anis; Ahmad Basri, Nadzirah; Md Rosli, Ahmad Nabil; Abdullah, Aszrin; Sulaiman, Norhasmah (2021)
Background: An objective study to explore Malaysian Muslims' perceptions and beliefs towards mental health is important to understand the underlying factors that contribute to stigma and consequently reject ion towards mental health services. The Muslims' Perceptions and Attitudes towards Mental Health (M-PAMH) enables this study to be conducted. Objective: This study aimed to translate the M-PAMH in Bahasa Malaysia and cross-culturally adapt it to be used among Malaysian Muslims. Methods: Two forward and backward translations were carried out by independent translators. Expert committees evaluated the translated version to meet the population's suitability. Readability and suitability of the items were assessed through preliminary evaluation among 28 Malaysian Muslims sample (from various socio-economic status and age ranging from 18 to 63 years old) hosted on mobile messaging platform and their feedback were collected. Results: Additional items were developed and added into the scale according to the local beliefs which attribute mental health as a sign of poor relationship with God and punishment. Terms such as Shaykh, 'Ayn, Ruqya, Jinn and Qadar were changed to 'Ustaz; 'Hasad Dengki'. 'Rawatan Perubatan Islam; 'Makhuk Halus' and 'Takdir' respectively to adapt to the population's jargon. Traditional practice in the original scale such as the use of black seed was changed to the use of black pepper and kaffir lime to suit the local traditional practices. Conclusion: A culturally-adapted psychometric is important to identify the underlying beliefs associated with stigma and reject ion towards mental health services. and consequently useful for effective mental health literacy programs among Malaysian Muslims.